Psychosufistic Dimensions of Serat Sastra Gendhing: A Hermeneutic Study of Javanese Spiritual Psychology - Balighoh Nur Fitriyati, Hikmatun; Widagdo, Sungging (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2025)
Serat Sastra Gendhing, a didactic Javanese literary source written by Sultan Agung Hanyakrakusuma, combines Sufi Islamic and indigenous Javanese spiritual thought. This research wishes to expose the psycho-sufistic values found in Serat Sastra Gendhing, and discuss their relation with transpersonal psychology. The research employs a qualitative method with an interpretive-hermeneutic approach through library research on three main manuscript versions. The analysis was conducted thematically on eight macapat poetic forms supported by psychological and Sufi theories. The results show that Serat Sastra Gendhing contains three central psycho-sufistic values: (1) existential awareness through sangkan paraning dumadi, which reflects the origin and purpose of human life; (2) self-control through aja dumeh and eling lan waspada; and (3) cosmic awareness through memayu hayuning bawana, which emphasizes harmony between humans, nature, and God. These three values represent the stages of spiritual consciousness development aligned with the concepts of self-awareness, self-regulation, and self-transcendence in transpersonal psychology. The study concludes that Serat Sastra Gendhing is a psycho-sufistic work that integratively unites Islamic spirituality, psychology, and Javanese culture.